Phylogeography, Population Structure, and Species Delimitation in Rockhopper Penguins (Eudyptes chrysocome and Eudyptes moseleyi). (18th November 2019) - Mays, Herman L; Oehler, David A; Morrison, Kyle W; Morales, Ariadna E; Lycans, Alyssa; Perdue, Justin; Battley, Phil F; Cherel, Yves; Chilvers, B Louise; Crofts, Sarah; Demongin, Laurent; Fry, W Roger; et al.
Abstract: Rockhopper penguins are delimited as 2 species, the northern rockhopper ( Eudyptes moseleyi ) and the southern rockhopper ( Eudyptes chrysocome ), with the latter comprising 2 subspecies, the western rockhopper ( Eudyptes chrysocome chrysocome ) and the eastern rockhopper ( Eudyptes chrysocome filholi ). We conducted a phylogeographic study using multilocus data from 114 individuals sampled across 12 colonies from the entire range of the northern/southern rockhopper complex to assess potential population structure, gene flow, and species limits. Bayesian and likelihood methods with nuclear and mitochondrial DNA, including model testing and heuristic approaches, support E. moseleyi and E. chrysocome as distinct species lineages with a divergence time of 0.97 Ma. However, these analyses also indicated the presence of gene flow between these species. Among southern rockhopper subspecies, we found evidence of significant gene flow and heuristic approaches to species delimitation based on the genealogical diversity index failed to delimit them as species. The best-supported population models for the southern rockhoppers were those where E. c. chrysocome and E. c. filholi were combined into a single lineage or 2 lineages with bidirectional gene flow. Additionally, we found that E. c. filholi has the highest effective population size while E. c. chrysocome showed similar effective population size to that of the endangered E. moseleyi . We suggest that the current taxonomic definitions within rockhopper penguins be upheld and that E. chrysocome populations, all found south of the subtropical front, should be treated as a single taxon with distinct management units for E. c. chrysocome and E. c. filholi .